Effectiveness of chest physiotherapy in stabilizing breathing rate in children with upper respiratory tract infections - Syamsidar Syamsidar; Trimaya Cahya Mulat; Heru Supriyatno (Journal Interdisciplinary Health, 2025)
Introduction: Acute Respiratory Tract Infections (ARTIs) remain a leading cause of morbidity and mortality among children, particularly in developing countries. Elevated respiratory rate is a common clinical manifestation in pediatric ARTI cases, often resulting from airway obstruction due to mucus accumulation. Chest physiotherapy is a non-pharmacological intervention aimed at mobilizing secretions, improving ventilation, and reducing respiratory effort. This study aimed to evaluate the effectiveness of chest physiotherapy in stabilizing the respiratory rate in preschool children diagnosed with ARTI. Methods: This case study involved two pediatric inpatients aged 1 and 3 years with a confirmed diagnosis of ARTI at Sandi Karsa Hospital, Makassar. Each patient received daily chest physiotherapy including percussion, vibration, and postural drainage for three consecutive days. Respiratory rate was measured before and after each session using direct observation and timing methods.. Results: A consistent reduction in respiratory rate was observed in both patients following each chest physiotherapy session. The average decrease ranged from 8 to 9 breaths per minute, indicating a significant clinical improvement. No adverse effects were reported during or after the intervention. Conclusion: Chest physiotherapy is an effective and safe non-pharmacological intervention for stabilizing the respiratory rate in children with ARTI. It facilitates mucus clearance, improves pulmonary ventilation, and alleviates respiratory effort. This intervention is recommended for integration into pediatric respiratory care protocols in hospital settings